PREPARATION AND IN VIVO EVALUATION OF CANDESARTAN CILEXETIL SOLID DISPERSIONS - KUMAR, UPPULURU ASHOK; SURESH, GANDE (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The present study aims at development of solid dispersions (SD) of candesartan cilexetil for enhanced solubility and bioavailability. Methods: About 18 SD formulations of candesartan cilexetil were prepared by solvent evaporation technique and evaluated. The in vitro release studies were conducted and the best formulation chosen was further characterized for Fourier transform infrared spectroscopy, Scanning electron microscope, X-ray, and stability. The in vivo evaluation study conducted in rats. Results: The formulation SD16 containing drug and Soluplus in 1:3 ratio along with 2% selective laser sintering was chosen optimal based on drug content (99.08%), and drug release (99.7%). In vivo studies conducted on SD16 showed that mean time to peak concentration (Tmax) was 2.0±0.05 and 4±0.2 h for the optimized and pure drug, respectively, while mean maximum drug concentration (Cmax) was 570.63±2.65 ng/mL and was significant as compared to the candesartan pure drug 175.146±0.07 ng/mL. Area under curve AUC0-∞ infinity for candesartan SD16 was higher (4860.61±1.05 ng.h/ml) than pure drug suspension 1480±1.72 ng.h/ml. Conclusion: Hence, the developed SD formulations enhanced the bioavailability of drug by 3 folds.